Determination Of Sugar Composition Of Selected Sugar Sweetened Beverages (SSBs) And Snack Foods In Kelantan - Hamid, Noor Fadzlina; Jalil, Rohana Abdul; Hashim, Roziyani; Mohd, Amira Suriyati; Ishak, Wan Rosli Wan; Nyi, Nyi Naing; Pachotikarn, Chanida; Prapkree, Lukkamol; Rueangsr, Narisa; Yamamoto, Shigeru (2018)
Sugars are important ingredients for the sugar sweetened beverages (SSBs) and snack foods industries. All sugars provide sweet taste but the intensity, quality and temporal profile of the sweeteners varies by type of sugar. The objective of this study was to determine sugar composition and it would contribute to the development of Malaysia database sugar composition table. Enzymatic technique was used to determine sugar composition in SSBs and snack foods, where combination of enzymes in sequential was used. The results showed the amount of isomerized sugar was found predominant in some beverages and minor in snack foods. However, the sucrose was the major component of total sugar in all of the SSBs and snack foods. The maltose level was the highest in instant chocolate malt drink and ground peanut cookies for SSBs and snack foods, respectively. The galactose levels in all samples were found to be very little. Lactose content was high in dairy products and snack foods samples such as chocolate coated, chocolate spread, chocolate nugget, chocolate coated wafer, milk chocolate coated wafer and chocolate rice cereal. The highest total sugar was found in instant coffee milk (60.65±3.13 g/100ml) for SSBs and milk chocolate coated (63.69±2.25 g/100g) for snack foods. In general, these findings suggested that total sugar composition of the food packaging items did not only indicate of sucrose as sugar content but also include either glucose, fructose, maltose, galactose or lactose. This information need to be disseminated to the public to increase awareness about the total sugar on food labels.